2015
DOI: 10.1016/j.cyto.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines regulate the expression of glycosyltransferases involved in the biosynthesis of tumor-associated sialylated glycans in pancreatic cancer cell lines

Abstract: The inflammatory microenvironment can modulate the glycosylation pattern of PDAC cells, increasing the expression of tumor-associated sialylated antigens such as SLe(x), which contributes to pancreatic tumor malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 64 publications
(63 reference statements)
3
33
0
Order By: Relevance
“…Our previous study has shown that NCOA3 upregulates the expression of fucosyltransferase 8 (FUT8) in PC cells. Fucosyltransferase expression in PC is associated with the increased expression of sialyl-Lewis a/x on the cancer cells [54], which act as the ligands for the selectins, present on the surface of endothelial cells, therefore, facilitating the interaction between cancer and endothelial cells during extravasation step of metastasis [54]. Further, fucosylation is also associated with the stem cell-like phenotype and the malignant transformation of intraductal papillary mucinous lesions [55].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study has shown that NCOA3 upregulates the expression of fucosyltransferase 8 (FUT8) in PC cells. Fucosyltransferase expression in PC is associated with the increased expression of sialyl-Lewis a/x on the cancer cells [54], which act as the ligands for the selectins, present on the surface of endothelial cells, therefore, facilitating the interaction between cancer and endothelial cells during extravasation step of metastasis [54]. Further, fucosylation is also associated with the stem cell-like phenotype and the malignant transformation of intraductal papillary mucinous lesions [55].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, note that the novel proinflammatory biomarker GlycA has been shown to be positively related to Lp-PLA 2 in subjects without T2DM or the metabolic syndrome (39). In view of the effect of Lp-PLA 2 to increase ILs, which are able to enhance protein glycosylation (40)(41)(42)(43), it is conceivable that Lp-PLA 2 could be involved in the association of sodium intake with plasma GlycA concentrations.…”
Section: Figure 1 Association Between Sodium Excretion (Mmol/24-h) Andmentioning
confidence: 96%
“…Pro-inflammatory cytokines can increase the expression of glycosyltransferases involved in the biosynthesis of cancer-associated antigens in pancreatic and gastric cancer cell lines [143, 144]. …”
Section: Tumour Promoting Inflammationmentioning
confidence: 99%